Analisa kualitas pelayanan guru terhadap kepuasan siswa dengan metode Servqual - Rapa, Imelda Cenda; Cahyono, Wahyu Eko; Fais, Moh Ainul (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze teacher service quality towards student satisfaction at SMP Al Huda Surabaya using the SERVQUAL method. Five dimensions of SERVQUAL (Tangibility, Reliability, Responsiveness, Assurance, Empathy) are used to measure the gap between student expectations and perceptions. A quantitative descriptive approach was applied with a sample of 70 students selected through simple random sampling. Data were collected using a valid and reliable questionnaire (Cronbach's Alpha: 0.941). The results showed similarities in all dimensions, with the largest gap in Tangibility (-0.69) and Reliability (-0.87). The largest gap was in the ability to explain the material (-1.02) and teacher attendance on time (-1.05). Recommended strategies include teacher training to improve competence, provision of learning facilities, and strengthening teacher-student interaction. This study contributes to improving the quality of education at SMP Al Huda Surabaya and becomes a reference for other institutions to improve student satisfaction.